Kecemasan Neurotik Tokoh Utama pada Novel Sumingkir dan Jadie : Tangis Tanpa Suara : Penelitian Sastra Bandingan - Nur Istikhomah; Surana Surana (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Sumingkir and Jadie : Tangis Tanpa Suara are two different novels that share the same theme, namely neurotic anxiety experienced by the main character. Based on this, the study used Sigmund Freud’s literary psychology approach with the comparative methods. The purpose of this study is to explain the neurotic anxiety experienced by each of the main character in the two novels. This study is qualitatively comparative descriptive. Data sources come from two novels, namely Sumingkir and Jadie : Tangis Tanpa Suara. Data is listed from dialogues and narratives depicting the neurotic anxiety of the main character. Data collection techniques are library studies with reading and recording techniques. Research data are identified, classified, analyzed, and summarized according to the problem formulation. The results of the study show that there are two similarities in the forms of neurotic anxiety in the two novels, namely (1) social neurotic anxiety. Then, (2) neurotic anxiety about losing, losing a job in Sumingkir’s and losing a loved one in Jadie’s. In addition, the form of neurotic anxiety in the two novels is different, namely anxiety for the future in Sumingkir’s. Meanwhile, worry about six years old in Jadie’s novels : Tangis Tanpa Suara.